2022
DOI: 10.3390/nu14245241
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Food Texture Modification among Individuals with Cerebral Palsy: The Challenges among Cerebral Palsy Families

Abstract: Individuals with cerebral palsy (CP) frequently present with multiple feeding problems, which may require food texture modification to ensure safe feeding. This review aims to explore the challenges individuals with CP and their caregiver’s face and recommend modified food textures to ensure safety and improve the quality of life and nutritional status. A systematic search was carried out through four databases (i.e., EBSCO (Medline), PubMed, Science Direct, and Web of Science) between January 2011 and May 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
0
0
Order By: Relevance
“…In the current study, we concluded that the feeding attitudes of children with CVI and CP were worse and that this was related to sensory processing skills. We think that this situation is related to the inability to tolerate the type, taste, and texture of foods, together with sensory reasons [55]. Although we focused on the relationship of feeding with sensory processing skills and oral and tactile stimuli in our study [56,57], it should be considered that motor, oral motor, swallowing, and chewing disorders also affect feeding in children with CP with and without CVI.…”
Section: Discussionmentioning
confidence: 90%
“…In the current study, we concluded that the feeding attitudes of children with CVI and CP were worse and that this was related to sensory processing skills. We think that this situation is related to the inability to tolerate the type, taste, and texture of foods, together with sensory reasons [55]. Although we focused on the relationship of feeding with sensory processing skills and oral and tactile stimuli in our study [56,57], it should be considered that motor, oral motor, swallowing, and chewing disorders also affect feeding in children with CP with and without CVI.…”
Section: Discussionmentioning
confidence: 90%